Aplikasi Mengkudu Sebagai Sumber Antioksidan Untuk Mengatasi Stress Ayam Broiler Di Daerah Tropis - E Syahruddin; H Abbas; E Purwati; Y Heryandi (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2012)
The study was conducted to test the effects of antioxidants levels (0, 500, 1000 and 1500 ppm) in fruit juice noni for broiler response in different room temperature (20°C, 26°C and 32°C). Research material consist of: 360 tail of two-week old broilers strains Acress Arbor. Research over the past eight weeks (from June 18, 2010 to August 13, 2010). The basic design CRD Split plot models of 3x4 and 3 replicates with 10 chickens for each box, as the main plot: Room temperature (20 : 26 and 32ºC), and Sub plot: level of antioxidants in the fruit juice noni (0:500:1000 and 1500 ppm). The data obtained were statistically analyzed using the SAS program package, and if it show any real effect followed by Duncans test/DMRT. Variables measured were feed consumption, feed conversion and levels of hormone thyroxine and fabrisius bursa weights of broiler. The results showed that fruit juice noni reduce heat stress in chickens by administering 500 ppm antioxidants of fruit juice noni in the drinking water of chickens that are kept at temperature of 26ºC and 1000 ppm at a temperature of 32ºC to increase levels of the hormone thyroxine, fabrisius bursa and feed consumption, feed conversion equal with controls.